Freakish patterns – species and species concepts in apomicts. (18th June 2013) - Haveman, Rense
<x xml:space="preserve">Abstract</x> Apomict groups keep challenging taxonomists, in classifications as well as in more fundamental question about the nature of apomictic species. The latter question is not just an academic one, because the outcome influences practical decisions on biodiversity and conservation. A historical overview over the species problem shows that a period of confusion and proliferation of species concepts between 1940 and 1990 was followed by an increasing consensus at the end of the 20th century that the species category is heterogeneous. Species come in kinds, which is understandable in light of their different evolutional histories. Recently, Wilkins stated that we do not need a generally applicable species concept, because species are not an a priori category into which all biological organisms must fit, but salient phenomena that are to be explained. Not only biparental, but also asexual organisms often form such species‐as‐phenomena, explained as some combination of adaptation to an ecological niche and reproductive compatibility. The above is illustrated by historical and current studies in three well‐studied apomict groups, viz. Ranunculus cassubicus agg., Rubus subgen. Rubus and Hieracium (subgen. Hieracium and Pilosella). Species in the Ranunculus cassubicus aggregate are the few existing sexuals, which are surrounded by a hybrid swarm of only partial apomictic forms, whereas in Rubus subgen. Rubus and Hieracium s.s. sexuals as well as numerous apomicts form well defined species. How species should be circumscribed in Pilosella is yet to be clarified. Largely, the differences between these groups can be contributed to their different modes of apomixis and the associated retained sexuality. From this review it is clear that the question is not so much 'What is a species?', but 'What is a species in this particular group?' To answer this question a thorough knowledge and understanding of the biology of the genus in question is required.